2014
DOI: 10.1007/s00606-013-0976-6
|View full text |Cite
|
Sign up to set email alerts
|

Distance between south-European and south-west Asiatic refugial areas involved morphological differentiation: Pinus sylvestris case study

Abstract: The phenotypic differentiation of relic P. sylvestris in southern Europe and southwestern Asia was verified using thirty-two populations sampled from the Iberian Peninsula, Massif Central, Balkan Peninsula, Crimea and Anatolia. Twenty-one morphological and anatomical needle traits and 18 cone morphological characteristics were examined to describe the population diversity and differentiation. The needle characters were not correlated to those of cone. The differences between regions were significant based on 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…This finding is significant because it shows that functional trait covariation known from interspecific scale may occur in a relatively homogenous genetic background suggesting that it results from a fundamental evolutionary trade‐off. Research in warmer, more southerly parts of P. sylvestris range might further probe the generality of this pattern, although we foresee that at lower latitudes, the relationship of longevity with structure may not hold as closely as needle longevity never decreases below two seasons (Reich, ; JO personal observation) while trait variation is extensive but may be attributed to the occurrence of additional climatic stressors, such as drought or to genetic isolation of populations (Jasińska et al., ).…”
Section: Discussionmentioning
confidence: 96%
“…This finding is significant because it shows that functional trait covariation known from interspecific scale may occur in a relatively homogenous genetic background suggesting that it results from a fundamental evolutionary trade‐off. Research in warmer, more southerly parts of P. sylvestris range might further probe the generality of this pattern, although we foresee that at lower latitudes, the relationship of longevity with structure may not hold as closely as needle longevity never decreases below two seasons (Reich, ; JO personal observation) while trait variation is extensive but may be attributed to the occurrence of additional climatic stressors, such as drought or to genetic isolation of populations (Jasińska et al., ).…”
Section: Discussionmentioning
confidence: 96%
“…Our hypothesis is that natural populations in the refugial areas, in addition to possessing imprints of historical events, are also distinctive due to adaptations to different habitat extremes on the periphery. This hypothesis is supported by studies performed on populations from Central and Northern Europe, the Balkans, Iberia, and Anatolia (Staszkiewicz, 1961;Tobolski & Hanover, 1971;Mejnartowicz, 1979;Prus-Glowacki & Stephan, 1994;Alía et al, 2001;Prus-Głowacki et al, 2003;Turna, 2003;Labra et al, 2006;Bilgen & Kaya, 2007;Pyhäjärvi et al, 2007;Semiz et al, 2007;Dzialuk et al, 2009;Jasińska et al, 2014). Based on these works, it can be concluded that populations in refugial areas display not only 'geographic marks', but also genetic differences and differentiation at the phenotypic level.…”
Section: Introductionmentioning
confidence: 82%
“…Oleksyn et al (1998) suggested that new models in predicting species' adaptation to the changing environmental conditions needs study on intrespecific differentiation level. Cone characteristics are traits of the highest discriminating power in inter-populational comparisons among regions in the works by Bobowicz and Korczyk (2000) and Jasińska et al (2014). In work of Androsiuk et al (2011), the principal variables which proved to be indicative to discriminate populations were the needle characteristics.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some of the valley and basin became the refugium for P. yunnanensis to survive on Quaternary glaciation (Grant 1977). When the climate became warm, multiple P. yunnanensis refugium populations spread to the Yunnan-Guizhou Plateau, while the barriers for effective gene flow within some sites were unfavorable for pines during the glacial and interglacial periods of the Pleistocene era (Jasinska et al 2014), which made the origin of P. yunnanensis unclear (Jin and Peng 2004). The early virgin forests of P. yunnanensis nearly disappeared because of disafforestation.…”
Section: Discussionmentioning
confidence: 98%